Thermal Performance of Solar Cooker Based on Evacuated Tube Collector and PCM Storage Unit - Saini, Surjeet; Kumar, Narender (Asian Review of Mechanical Engineering, 2017)
In this experimental set up, solar cooker with thermal storage unit was connected to evacuated tube collector through connecting pipes via a low flow rate pump. The design of solar cooker was such that the following fluid transfers its heat to PCM and cooking vessel simultaneously. Commercial grade acetanilide was used as latent heat storage material in the solar cooker. Cooking experiments were conducted during noon and evening with different loads and PCM storage processes were carried out simultaneously. The result include that cooking lunch for a family is possible simultaneously with heat storage along the day. Closing gate valves afterward allows cooking the dinner with the retained heat up to late evening. This expands the applicability of solar cooking and sustains the possibility of all the day around cooking using solar energy with a low inventory cost.